2021
DOI: 10.1017/s0033291721003378
|View full text |Cite
|
Sign up to set email alerts
|

Independent contribution of polygenic risk for schizophrenia and cannabis use in predicting psychotic-like experiences in young adulthood: testing gene × environment moderation and mediation

Abstract: Background It has not yet been determined if the commonly reported cannabis–psychosis association is limited to individuals with pre-existing genetic risk for psychotic disorders. Methods We examined whether the relationship between polygenic risk score for schizophrenia (PRS-Sz) and psychotic-like experiences (PLEs), as measured by the Community Assessment of Psychic Experiences-42 (CAPE-42) questionnaire, is mediated or moderated by lifetime cannabis use at 16 years of age in 1740 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 63 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…PRS performs worse when the sample consists of individuals from different ancestries (Andreassen et al 2023), however our sample consisted mainly of white European individuals. A previous ALSPAC study did not find any association between schizophrenia PRS and psychotic experiences (Jones et al 2016), while other studies with larger samples have found associations between schizophrenia PRS and psychotic-like experiences (Barbu et al 2023;Elkrief et al 2023).…”
Section: Discussionmentioning
confidence: 63%
“…PRS performs worse when the sample consists of individuals from different ancestries (Andreassen et al 2023), however our sample consisted mainly of white European individuals. A previous ALSPAC study did not find any association between schizophrenia PRS and psychotic experiences (Jones et al 2016), while other studies with larger samples have found associations between schizophrenia PRS and psychotic-like experiences (Barbu et al 2023;Elkrief et al 2023).…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, research evidence on the psychological consequences of the exposure to trauma, including adverse childhood experience, are not limited to PTSD (Elkrief et al. , 2021 ; Marchi et al. , 2022b , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2021) reported in the European IMAGEN cohort that cannabis use and genetic liability for schizophrenia were associated with more frequent psychotic experiences, and there was no evidence of mediation or moderation between these two predictors (Elkrief et al, 2021). Similarly, Wainberg et al (2021) examined a large sample from the UK Biobank and found that cannabis users with high schizophrenia genetic liability were more likely to report psychotic experiences, as well as hallucinations, and delusions of reference (Wainberg et al, 2021).…”
Section: Psychopathology Of Cannabis-associated Psychosis and Its Gen...mentioning
confidence: 99%